MEASURING THE COMPETENCE AND THE INDEPENDENCE OF AD HOC COMMITTEE AND ITS EFFECT ON THE PERFORMANCE OF GENERAL ELECTION - Arif, Ahmad (Terbuka Journal of Economics and Business, 2020)
The success of the election is very closely related to the way each election is held and carried out correctly. The human resource factor (SDM) is not only regarded as the determination of the success of election but also as the quality of the general election and democracy. The process of a general election in 2019 has been found that the ad hoc committee faced many obstacles, which were generally related to the voter data collection process, election socialization, voting and counting process, the recapitulation of the voting election, etc. To improve the quality of human resources in conducting the elections was necessary to be appropriately implemented in which it must be directed and planned. However, it became a significant barrier to a large number of ad hoc (temporary) committees. This research aimed to see the competence and independence of the ad hoc committee in the 2019 Simultaneous Elections in the City of Depok. This research used descriptive quantitative in which it was based on survey results, document reviews, and observations. The results showed that the competence and independence of the ad hoc committee effected significantly to support the success of the general election.